Pendidkan Sebagai Usaha Membentuk Perilaku Terpuji Yang Mencerminkan Pengamalan Asmaul Husna Al-Jaami’, Al-Akhir, Al-Adl Dalam Kehidupan Sehari-Hari Pada Siswa Di Madrasah - Muliatih Muliatih (Al Yazidiy Jurnal Sosial Humaniora dan Pendidikan, 2023)
Educational institutions such as schools teach students to always behave with good and commendable behavior or noble character through the subjects listed in the curriculum. Some of the commendable behavior taught in school is how to behave fairly (Al-Adl), always be united and get along in a good way (Al-Jaami) and leaving the final outcome only to Allah SWT. (Al-Akhir) Because in fact the end of the end belongs only to our Lord, all causes and ends of the path will lead to Allah alone.